Sustained-release calcium antagonist in patients over 60 years with isolated and systolo-diastolic arterial hypertension - V. E. Oleynikov; V. A. Budanova; E. E. Grishaeva; E. I. Yastrebova; S. S. Fadeeva; L. I. Gusakovskaya (Кардиоваскулярная терапия и профилактика)
Aim. To study antihypertensive and organo-protective effects of a calcium antagonist (CA), controlled-release (CR) nifedipine, in patients over 60 years with Stage I-II isolated systolic and systolo-diastolic arterial hypertension (ISAH, SDAH).Material and methods. This 24-week open prospective study included 48 patients aged over 60 years with Stage I-II AH. SDAH and ISAH participants received nifedipine SR in the dose of 40 mg/d. Treatment effectiveness was assessed by dynamics of office blood pressure (BP) and 24-hour BP monitoring (BBP) parameters. Organoprotective effect was assessed by dynamics of echocardiography parameters and microalbuminuria (MAU) levels.Results. Nifedipine SR therapy was associated with substantial BP reduction and improved circadian BP profile in all participants; reduced myocardial hypertrophy in elderly people; normalisation of left ventricular (LV) diastolic function and decreased number of patients with MAU in both groups, especially among those with ISAH.Conclusion. Complex assessment of nifedipine SR clinical effectiveness in ISAH and SDAH patients aged over 60 years demonstrated multiple effects on AH-related parameters and improved circulatory functioning in elderly patients. Nifedipine SR is a medication of choice in ISAH patients.